2020
DOI: 10.1177/2472630320921130
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Transfer Difference in Characterization of Glycosaminoglycan-Protein Interactions

Abstract: Novel methods in nuclear magnetic resonance (NMR) spectroscopy have recently been developed to investigate the binding properties of intermolecular complexes endowed with biomedical functions. Among these methods is the saturation transfer difference (STD), which enables the mapping of specific binding motifs of functional ligands. STD can efficiently uncover the specific and preferential binding sites of these ligands in their intermolecular complexes. This is particularly useful in the case of glycosaminogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…There are three main goals in using NMR to study GAG-protein interactions: the first is to detect the amino acids involved in binding from the perspective of proteins, the second is to analyze the saccharide and its groups involved in binding from the perspective of GAGs, and the third is to observe the conformational changes and kinetic information during binding from the perspective of the interaction. To achieve these three goals, three technologies, chemical shift perturbation (CSP), saturation transfer difference (STD), and exchangetransferred nuclear Overhauser effect (trNOE), are initially used (Vignovich and Pomin, 2020), while other technologies, such as saturation transfer double difference (STDD) (Ledwitch et al, 2016), paramagnetic relaxation enhancement (PRE) (Orton et al, 2016), pseudocontact shifts (PCS) (Srb et al, 2019), and exchange-transferred rotating-frame Overhauser effect (ROE), have been developed to compensate for the shortcomings of the former. The latest pulse sequences have been developed to provide a more detailed and accurate description of the binding process, such as the gradient spectroscopic observation of water ligands (waterLOGSY) (Huang and Leung, 2019) and heteronuclear in-phase single quantum coherence experiment (HISQC) (Sepuru et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…There are three main goals in using NMR to study GAG-protein interactions: the first is to detect the amino acids involved in binding from the perspective of proteins, the second is to analyze the saccharide and its groups involved in binding from the perspective of GAGs, and the third is to observe the conformational changes and kinetic information during binding from the perspective of the interaction. To achieve these three goals, three technologies, chemical shift perturbation (CSP), saturation transfer difference (STD), and exchangetransferred nuclear Overhauser effect (trNOE), are initially used (Vignovich and Pomin, 2020), while other technologies, such as saturation transfer double difference (STDD) (Ledwitch et al, 2016), paramagnetic relaxation enhancement (PRE) (Orton et al, 2016), pseudocontact shifts (PCS) (Srb et al, 2019), and exchange-transferred rotating-frame Overhauser effect (ROE), have been developed to compensate for the shortcomings of the former. The latest pulse sequences have been developed to provide a more detailed and accurate description of the binding process, such as the gradient spectroscopic observation of water ligands (waterLOGSY) (Huang and Leung, 2019) and heteronuclear in-phase single quantum coherence experiment (HISQC) (Sepuru et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The 15 N-HSQC spectrum of CS titration showed that in addition to the BBXB motif in the 40 s loop, the CCL5 dimer also has a CS binding epitope located in the N loop, including the R17, L19 and I15 residues (Deshauer et al, 2015). By comparing the NMR spectra of the saturated state (on-resonance) and unsaturated state (off-resonance) of the interaction between the protein and the ligand in the solution (Vignovich and Pomin, 2020), the STD method can determine how GAG binds to protein during the formation of the GAG-protein complex. Yu et al (2014) used saturated STD NMR to characterize the interaction of a synthesized heparin octasaccharide with FGF-2 and FGF-10.…”
Section: Nmrmentioning
confidence: 99%
“…The last section of this special issue deals with glycan–protein interactions, which require prior knowledge of primary structures and so are a step closer to functional studies of carbohydrates. Vignovich and Pomin 8 review saturation difference (STD) NMR spectroscopy to study the interactions of glycosaminoglycans with proteins. STD specifically allows the determination of which parts of the ligand interact with the protein, which is significant for the study of structure–activity relationships.…”
Section: Glycan–protein Interactionsmentioning
confidence: 99%